Characterization of Tyrosinase Inhibitors in Dryopteris crassirhizoma Rhizome Using a Combination of High-Speed Counter-Current Chromatography, Affinity-Based Ultrafiltration, and Liquid Chromatography–Tandem Mass Spectrometry - Wang, Zhiqiang; Wang, Ning; Han, Dandan; Yan, Hongyuan (Frontiers in Nutrition, 2022)
Dryopteris crassirhizoma rhizome (DCR) inhibits melanin production in B16F10 melanoma cells and tyrosinase activity. The melanin content and tyrosinase activity of DCR-treated zebrafish embryos were determined to evaluate the in vivo inhibitory effect of DCR on melanogenesis. Moreover, an off-line hyphenated method combining high-speed counter-current chromatography, affinity-based ultrafiltration, and liquid chromatography–tandem mass spectrometry was used to identify and characterize the DCR compounds with tyrosinase inhibitory activity. Our results indicated that, DCR significantly decreased the melanin content and tyrosinase activity in zebrafish embryos in a dose-dependent manner; moreover, 22 compounds in DCR presented tyrosinase inhibitory activity. In silico molecular docking prediction data indicated that the 22 compounds in DCR can form stable conformations in the active site pocket of tyrosinase.